Feasibility of a social network in Tourism Higher Education - Salgado, Manuel (2012)
The following article analyses the organization network of Higher Education Institutions in the area of Tourism in Portugal and the interest in creating a social network in this field, which contributes to the cohesion and communication of this scientific community. As a result, the project “National Observatory of Tourism Education” is introduced, intending to build a technologic work platform, for this particular academic community, with the purpose of building an efficient and organized network, allowing the sharing of knowledge and relevant experiences at a national and regional level, generating added value that allows us to show the major role that education plays in Tourism. We also studied how we could use the social networks in behalf of the educational science, taking advantage of their particularities, in an effort to show how they are changing the face of modern Tourism, in order to justify the possible need to create a social network on Tourism in the Central Region.